2014
DOI: 10.2174/1871527312666131223114457
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Activity-Regulated Wnt Signaling in Synaptic Plasticity, Glial Function and Chronic Pain

Abstract: Wnt signaling pathways are master regulatory networks in a variety of developmental and oncogenic processes. In the nervous system, Wnt signaling pathways are known to regulate neuronal morphogenesis and synaptic differentiation. Aberrant Wnt signaling is implicated in various neurological diseases. Recent studies have revealed that the activity of Wnt signaling pathways is critically controlled by synaptic activity. The activity-regulated Wnt signaling plays an important role in the expression of synaptic pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 78 publications
1
16
0
1
Order By: Relevance
“…Consistent with this, we demonstrated here the co-labeling of TLR4 and Iba-1, a microglial marker. Microglia is the resident macrophage in the brain that detects external information and release a large number of inflammatory factors (Tang, 2014), We previously reported that visceral hypersensitivity was involved in microglial activation, IL-1β and TNF-α accumulation in the PVN (Chen et al, 2015). Consistent with these data, the present study determined that visceral hypersensitivity was involved in an increase in PVN IL-1β and TNF-α protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, we demonstrated here the co-labeling of TLR4 and Iba-1, a microglial marker. Microglia is the resident macrophage in the brain that detects external information and release a large number of inflammatory factors (Tang, 2014), We previously reported that visceral hypersensitivity was involved in microglial activation, IL-1β and TNF-α accumulation in the PVN (Chen et al, 2015). Consistent with these data, the present study determined that visceral hypersensitivity was involved in an increase in PVN IL-1β and TNF-α protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, alterations of Wnt canonical signaling pathway functionally lead to diverse neuropathologies and neurodevelopmental dysfunctions, such as altered synaptic plasticity, that have been reviewed by Inestrosa et al (2015) and Tang et al (2014) . Indeed, Wnt signaling pathway dysfunctions are involved in the etiopathogenesis of various neurological diseases such as chronic pain, cerebral ischemia, Huntington disease, amyotrophic lateral sclerosis and other neurodegenerative pathologies . Wnt alterations in schizophrenia could be through roles of this signaling pathway in neuronal migration, survival, and/or apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…Wnt ligands bind frizzled receptors and coreceptors and signal through canonical β-catenin-dependent pathways and noncanonical β-catenin–independent pathways. Dysregulation of Wnt signalling is implicated in various neurological diseases 149 . Recent studies have demonstrated a critical role of Wnt signalling in the pathogenesis of neuropathic pain and cancer pain in rodents 148, 149 .…”
Section: Other Emerging Targets That Modulate Neuroinflammationmentioning
confidence: 99%
“…Dysregulation of Wnt signalling is implicated in various neurological diseases 149 . Recent studies have demonstrated a critical role of Wnt signalling in the pathogenesis of neuropathic pain and cancer pain in rodents 148, 149 . Nerve injury and bone cancer caused rapid and long-lasting upregulation of Wnts (e.g., Wnt3a, a prototypical Wnt ligand for the canonical pathway), as well as activation of Wnt/frizzled/β-catenin signalling – not only in primary sensory and spinal dorsal horn neurons but also in spinal astrocytes 148 .…”
Section: Other Emerging Targets That Modulate Neuroinflammationmentioning
confidence: 99%